Chemically Modified Multi-walled Carbon Nanotubes (MWCNTs) with Anchored Acidic Groups - Nuruzatulifah Asari @ Mansor,; Tessonnier, Jean-Philippe; Ali Rinaldi,; Reiche, Sylvia; M.G, Kutty (Universiti Kebangsaan Malaysia, 2012)
Surface functionalization of multi-walled carbon nanotubes (MWCNTs) was carried out using a gas phase treatment in a Universal Temperature Program (UTP) reactor by flowing SO3 gas onto the CNTs while being heated at different temperatures. The functionalized nanotubes were characterized using X-ray Fluorescence (XRF), Fourier Transform Infrared Spectroscopy (FT-IR) and Raman spectroscopy. The amount of oxyen and sulfur containing groups was determined by acid-base titration. The titration results were in good agreement with elemental analysis using x-ray fluorescence. FTIR analysis showed the presence of oxygen and sulfur containing groups, S=O, C-S, C=O and -COOH. Raman spectroscopy confirmed that oxygen and sulfur containing acidic groups covalently attached to the sidewall of the MWCNTs.